O‘ZBEKISTONDA AUTIZM DIAGNOSTIKASINING HOZIRGI HOLATI VA RIVOJLANISH ISTIQBOLLARI (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2025)
This article analyzes the current state of autism spectrum disorder (ASD) diagnostics in Uzbekistan, focusing on challenges and future development prospects. The study is based on V. Kagan’s work "Autism in Children" (1981) and the textbook "Special Pedagogy" (2020). Psychological and pedagogical aspects of diagnostics, early detection, and professional training are discussed. The findings indicate that the diagnostic system is developing, but further standardization, interdisciplinary collaboration, and public awareness are needed.